Factors in cyber bullying: the attitude-social influence-efficacy model - Lee, Yi Chih; Wu, Wei-Li (Anales de Psicología / Annals of Psychology, 2018)
This study examines the correlation between risk perception, knowledge, social influence, self-efficacy, and cyber bullying behavior from the perspective of the attitude-social influence-efficacy model. The samples in this survey are adolescents who have had cyber bullying behavior or have witnessed their peers’ cyber bullying behavior. The results showed that attitude towards cyber bullying affected cyber bullying intention, and that intention also influenced cyber bullying behavior. Social influence also had an impact on cyber bullying intention and cyber bullying behavior. In fact, intention was a mediator between attitude and behavior, as well as between social influence and behavior.